UNSTIMULATED SALIVARY FLOW RATE VARIATIONSDURING EARLY MIXED, LATE MIXED, AND PERMANENT DENTITION AND ITS ASSOCIATION WITH AGE, GENDER, & SOCIOECONOMIC CLASS AMONG HEALTHY CHILDREN-A CROSS SECTIONAL STUDY - Ansari, Asma Saher; Ahmed, Imtiaz; Anwar Qureshi, Masood; Muqaddas , Zairah; Rehman, Abdur (Journal of Ayub Medical College Abbottabad, 2026)
1) Roblegg E, Coughran A, Sirjani D. Saliva: An all-rounder of our body. Eur J Pharm Biopharm. 2019 Sep; 142:133-141. doi: 10.1016/j.ejpb.2019.06.016. Epub 2019 Jun 18. 2) Dawes C, Pedersen AL, Villa A, EkstrÃ¶m J, Proctor GB, Vissink A, Aframian D, McGowan R, Aliko A, Narayana N, Sia YW. The functions of human saliva: A review sponsored by the World Workshop on Oral Medicine VI. Arch. Oral Biol. 2015 Jun 1;60(6):863-74. 3) EkstrÃ¶m J, Khosravani N, Castagnola M, Messana I. Saliva and the control of its secretion. In Dysphagia 2017 (pp. 21-57). Springer, Cham.